A new development of eco-friendly Ultra-High performance concrete (UHPC): Towards efficient steel slag application and multi-objective optimization. (1st November 2021) - Fan, Dingqiang; Yu, Rui; Shui, Zhonghe; Liu, Kangning; Feng, Yuan; Wang, Siyu; Li, Keke; Tan, Junhui; He, Yongjia
Highlights: A novel method for designing an eco-friendly UHPC is presented. A DOD model for multi-object optimization of UHPC is built. A new UHPC efficiently incorporating steel slag is developed. The newly developed UHPC exhibits admirable ecological value. Abstract: This paper addresses an innovative method for the development of eco-friendly ultra-high performance concrete (UHPC), towards efficient steel slag application and synergetic optimization of multi-objective. Specifically, a D-optimal design (DOD) based regression model for property prediction with high goodness of fit (R 2  > 0.9) is established. Then, a new UHPC is designed by a numerical optimization method based on the established DOD model. Furthermore, to verify the merit of the designed UHPC, some important properties of the UHPC samples are evaluated. The obtained results reveal that the addition of steel slag powder (SSP) contributes to the improvement of UHPC workability, and the highest slump flow is 268 mm. In addition, the increase of SSP content is detrimental to the early compressive strength, but does not affect the later strength of UHPC (130 ± 2 MPa). Besides, the chloride penetration resistance of UHPC will decrease with the incorporation of SSP, but its anti-chloride permeability is still lower than ordinary concrete. Conclusively, it is demonstrated that the use of this statistical design method could not only benefit environmental protection but also produce a new green UHPC with excellent properties.